Social learning in Learning Networks through peer support: Research findings and pitfalls - Brouns, Francis; Hsiao, Amy (Proceedings of the International Conference on Networked Learning, 2012)
Learning Networks are particularly suitable for lifelong learners as Learning Networks are online social networks designed to support non-formal learning. Lifelong learners want to learn what they need, when they need it and at a place and pace that suits them. Combined with the heterogeneous background of the learners, it is very hard to meet these needs with traditional curriculum based formal education. Instead the learner needs to be put central. Moreover, learners in a LN need to rely on learning through and with others, by sharing knowledge. That this is a feasible option is shown by the positive effects of collaborative learning and peer tutoring in formal education, as well as the interest in social learning in the digital era. However, a Learning Network needs to provide learner support services to tackle obstacles that arise due to the lack of interaction structures and organisational structures that come naturally with a formal educational setting. A peer support service that assists learners in finding the most suitable peer for their request is one of the required learner support services. In this paper we argue why social learning and peer support are relevant to learners in a Learning Network. We describe our peer support model based on the notion of ad hoc transient groups and present findings of five empirical studies that used prototypical implementations of this model. In the first prototypes peer selection criteria focused on content knowledge, proximity or eligibility and past workload. As collaboration tools, a wiki, discussion forums or instant messaging were used. In three studies, both formal education and in Learning Network conditions, the peer support systems were successful in that selected peers provided decent answers. However in two other studies we encountered problems. In one study learners failed to use the peer support systems to ask questions. In another study, sufficient participants were recruited beforehand, but many never responded when the experiment started. As a consequence, peers who were paired with learners never showed up and learners got frustrated. This shows how important it is that learner support services not only provide the means to interact with others but also provide the affordances that stimulate and motivate the learners to engage in meaningful interactions.